ACTION OF DIPHTHERIA TOXIN IN THE GUINEA PIG - Baseman, Joel B. (The Rockefeller University Press, 1970)
The blood clearance and distribution in the tissues of (125)I after intravenous injection of small doses (1.5–5 MLD or 0.08–0.25 µg) of (125)I-labeled diphtheria toxin has been followed in guinea pigs and rabbits and compared with the fate of equivalent amounts of injected (125)I-labeled toxoid and bovine serum albumin. Toxoid disappeared most rapidly from the blood stream and label accumulated and was retained in liver, spleen, and especially in kidney. Both toxin and BSA behaved differently. Label was found widely distributed among all the organs except the nervous system and its rate of disappearance from the tissues paralleled its disappearance from the circulation. There was no evidence for any particular affinity of toxin for muscle tissue or for a "target" organ. Previous reports by others that toxin causes specific and selective impairment of protein synthesis in muscle tissue were not confirmed. On the contrary, both in guinea pigs and rabbits, a reduced rate of protein synthesis was observed in all tissues that had taken up the toxin label. In tissues removed from intoxicated animals of both species there was an associated reduction in aminoacyl transferase 2 content. It is concluded that the primary action of diphtheria toxin in the living animal is to effect the inactivation of aminoacyl transferase 2. The resulting inhibition in rate of protein synthesis leads to morphologic damage in all tissues reached by the toxin and ultimately to death of the animal.